The mind-body problem between philosophy and the cognitive sciences - Sandro Nannini (Rivista Internazionale di Filosofia e Psicologia, 2023)
Here, I examine the main philosophical solutions to the mind-body problem distinguishing between “historicist” solutions that (more or less clearly) separate philosophy from science and solutions that instead result from a double “cognitive turn”, and see “continuity” between philosophy of mind and the cognitive sciences. The “historicist” solutions include ontological dualism (together with “skepticism” and “new mysterianism”), epistemological dualism, subjective idealism, and absolute idealism. In this group, transcendental idealism, phenomenology, and neutral monism are the solutions most open to a dialogue between philosophy and science. The “naturalistic” solutions can be divided into four groups: (1) behaviorism (psychological, logical, philosophical-analytical behaviorism); (2) materialism (identity theory, physicalism); (3) “weak naturalism” (functionalism, anomalous monism, “biological naturalism”, liberal naturalism, emergentism); (4) “strong naturalism” (“cognitive neo-evolutionism”, eliminativism). These offer a physicalist-eliminative solution to the mind-body problem (here called “soft physicalistic eliminativism”) that allows for more continuity between philosophy of mind and the cognitive sciences.